Diagnosis of sarcopenia by evaluating skeletal muscle mass by adjusted bioimpedance analysis validated with dual‐energy X‐ray absorptiometry. Issue 6 (4th October 2021) - Cheng, Keith Yu‐Kin; Chow, Simon Kwoon‐Ho; Hung, Vivian Wing‐Yin; Wong, Carissa Hing‐Wai; Wong, Ronald Man‐Yeung; Tsang, Charlotte Sau‐Lan; Kwok, Timothy; Cheung, Wing‐Hoi
Abstract: Background: This study aimed to adjust and cross‐validate skeletal muscle mass measurements between bioimpedance analysis (BIA) and dual‐energy X‐ray absorptiometry (DXA) for the screening of sarcopenia in the community and to estimate the prevalence of sarcopenia in Hong Kong. Methods: Screening of sarcopenia was provided to community‐dwelling older adults. Appendicular skeletal muscle mass (ASM) was evaluated by BIA (InBody 120 or 720) and/or DXA. Handgrip strength and/or gait speed were assessed. Diagnosis of sarcopenia was based on the 2019 revised Asian Working Group for Sarcopenia cut‐offs. Agreement analysis was performed to cross‐validate ASM measurements by BIA and DXA. Multiple regression was used to explore contribution of measured parameters in predicting DXA ASM from BIA. Results: A total of 1587 participants (age = 72 ± 12 years) were recruited; 1065 participants were screened by BIA (InBody 120) with 18 followed up by DXA, while the remaining 522 participants were assessed by the BIA (InBody 720) and DXA. The appendicular skeletal muscle mass index (ASMI) evaluated by BIA showed a mean difference of 2.89 ± 0.38 kg/m 2 (InBody 120) and 2.97 ± 0.45 kg/m 2 (InBody 720) against DXA gold standard. A significant overestimation of muscle mass was measured by BIA compared with DXA ( P < 0.005). BIA data were adjusted using prediction equation and mean difference reduced to −0.02 ± 0.31 kg/m 2 in cross‐validation. Prevalence of sarcopenia in older adults ≥65 ranged from 39.4% (based on ASMI by DXA) to 40.8% (based on predicted DXA ASMI from BIA). Low ASMI by DXA was found in 68.5% of the older adults screened. The percentage of older adults exhibited low handgrip strength ranged from 31.3% to 56%, while 49% showed low gait speed. Conclusions: Bioimpedance analysis was found to overestimate skeletal muscle mass compared with DXA. With adjustment equations, BIA can be used as a quick and reliable tool for screening sarcopenia in community and clinical settings with limited access to better options.